Pembelajaran Berbasis Aktivitas Materi Operasi Pecahan dengan Menggunakan Visualisasi Gaptek - Memolo, Tundung (Jurnal Didaktika Pendidikan Dasar, 2021)
Activity-based learning is a student-centered learning process that involves mental and psychological aspects through a variety of experiences. This study used GAPTEK visualization, namely physical activities of lining, cutting, pasting, and calculating. The purpose of this study was to describe how activity-based learning of fraction operation material using GAPTEK visualization, to find out how much the percentage of student positive responses, and the effectiveness of the learning in grade 7 students of SMP Negeri 3 Kepil. The research method uses quasi-experimental research with data collection in the form of learning outcomes tests, observations and questionnaires. A significance value of 0.895> 0.05 indicates that the two groups are normally distributed and homogeneous. The significance value of the difference is 0.569> 0.05 which indicates that there is no difference between the pretest mean of the control and experimental groups. The learning description shows that students are actively involved in group discussions and share roles. The average percentage of students' positive responses related to activity-based learning about fraction operations using GAPTEK visualization was 95.3%. Activity-based learning has been effectively used, which is shown by the experimental class average of 74.33 exceeding the value of 70.00, and exceeding the average control class, namely 56.00. The difference in the increase in the average pretest and posttest experimental class was 37.33, more than the difference in the control class of 21.00.